Transformation of Life & Labor in Appalachia Volume Two - Lewis, Ronald L. (Appalachian State University, 1990)
This volume of the Journal of the Appalachian Studies Association includes a collection of essays exploring the industrialization of the Appalachians and the effect on the economy.